Regional cancer therapy (Humana Press, 2007)
This volume provides a biological and pharmacological background for regional cancer therapy, strategies and techniques for regional therapies, and specific indications and results for different tumor entities. Clinical trial concepts and detailed treatment protocols are also presented. This book is essential reading for researchers and clinicians engaged in seeking advanced therapeutic options for cancer patients worldwide.